Investor learning about monetary-policy transmission and the stock market - Andrei, Daniel; Hasler, Michael Nicolas (Elsevier BV, 2025)
We model how investor learning about monetary-policy transmission impacts asset prices. In an asset-pricing model, investors learn from realized inflation surprises how effectively monetary policy steers future inflation. Downward revisions in perceived effectiveness raise expected inflation persistence, increasing return volatility and risk premia. These effects intensify when policy deviates significantly from neutral or monetary transmission uncertainty is high. We estimate the model using U.S. macro and policy data from 1954 to 2023. The resulting dynamics align with observed patterns in equity returns and volatility. Empirical tests support the model’s core prediction: investor learning turns central-bank credibility into a priced risk factor.
Keywords: Asset pricing; Learning; Inflation; Monetary policy